Colon Volvulus: Disease or Consequence? - Martínez, Bertha Zenaida Acevedo; Jarquin, Javier López; Piña, Oscar Escalante; Ocampo, Carlos Isaac Cabrera; Sánchez, Uriel Saúl Canché; Guerrero, Lenin Guerrero; Ángeles, Bruno París Romero; Sánchez, Morelos Adolfo García (British Journal of Healthcare and Medical Research, 2025)
Introduction: Sigmoid colon volvulus is produced by torsion on itself, which causes an obstruction and endangers the blood supply to the organ and represents a condition because of another underlying pathology, the highest prevalence is in men over 70 years of age. Objective: Presentation of a case. Method: A 73-year-old man with paranoid schizophrenia under treatment presented to the emergency department for acute constipation of 72 hours, with no evacuation and flatus. She refers to abdominal distension of 48 hours prior in a sudden and evolutionary way, continuous abdominal pain of a colic type and generalized oppressiveness. An emergency exploratory laparotomy was performed initially, with the finding of volvulus of the giant sigmoid colon not perforated, but with intestinal ischemia. Intestinal resection of the sigmoid colon and stoma is performed. Discussion: Strangulated colon volvulus makes it a surgical emergency due to intestinal necrosis, septic shock and death; the computed tomography study is the gold standard for confirming the diagnosis of colon volvulus, surgical treatment is definitive. Conclusion: Sigmoid colon volvulus is a consequence of another pathology (such as benign prostatic hypertrophy) and not a disease. Its initial treatment (endoscopically) will depend on the time of evolution, infrastructure, expertise and/or each case. But at the end of the day, management is urgent, priority to scheduled, with partial resection of the colon, stoma, and/or bowel reconnection.